FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN GANGGUAN FUNGSI PARU PADA PEKERJA PEMBUAT KASUR (STUDI KASUS DI DESA BANJARKERTA KARANGANYAR PURBALINGGA) - Ratna Yuliawati (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2015)
Mattress maker is one of the high-risk job of lung function. Dust from the production of an effect on lung function. Research describe dust from production assosiated to the pulmonary dysfunction. Previous studies explain the illness rate reached 70% in workers who inhale cotton dust. Describe the various factors assosiated to the pulmonary dysfunction between age, nutritional status, years of service, the use of masks, ventilation, workplace ownership, and the amount of dust inhaled by the incidence of lung function, job characteristics, and the amount of dust inhaled by the mattress makers in the District Karanganyar Purbalingga. This study was an cross-sectional, with a total sample of 80 workers mattress maker. The independent variable in this study is a age, nutritional status, years of service, the use of masks, ventilation, workplace ownership, and levels of total particles inhaled. The analysis was performed using univariate, bivariate and multivariate as well as by calculating the ratio of prevalence. The results showed that there are 4 variables significantly associated with lung function. that workers exposed to dust> 0.2 mg/m3 per day with a ratio of 27.203 prevalent (95% CI = 1.885 to 39,257) Working period (≥ 10 years), with a ratio of 21,502 prevalent (95% CI = 9.559 to 483,65) The use of masks (not always use) with the ratio of 43.965 prevalent (95% CI = 2.831 to 682,80) Ownership separate workplaces with 27.583 prevalent ratio (95% CI = 1.955 to 389,25). The risk factors significantly associated with impaired lung function is inhaled dust particles, years of service, the use of masks and a separate work between sections. suggested to the labor department and the health department to conduct promotive and preventive so that workers can be maintained mattress maker of health and safety work